Nearpod Integration: Improving Analytical Skills In Natural Science Subject - Fitriani, Hikmah Yaumil; Agustin, Hikmasanti; Kholidya, Citra Fitri; Dwiningsih, Kusuma; Subagyo, Heru (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2024)
The purpose of this classroom action research is to describe the effectiveness of learning that integrates Nearpod Media to improve student analytical thinking skills regarding environmental pollution in the natural sciences. Regardless, the ability of analysis consists of three aspects, namely differentiating, organizing, and attributing, so that increasing analytical thinking skill is viewed from these three aspects. The subjects of this research are grade VII students at SMPN 29 Gresik. The research instruments used were questionnaire sheets and pre-test and post-test sheets in cycle I and cycle II. Meanwhile, the data analysis uses descriptive analysis, descriptive statistics, and a sample t-test. The research findings indicate that the learning process carried out by the students is very good. Effectiveness is shown by the pre-test and post-test scores for each aspect. Based on descriptive statistics, it is known that the skewness value ranges from -0.98 to 0.93 and the kurtosis value ranges from -0.002 to 1.63, which means normal data distribution. Furthermore, the T-test score is <alpha coefficient of 0.05, showing a significant difference in improving students' analytical skills after the treatment. Therefore, it can be concluded that using Nearpod media integrated into learning can effectively improve students' analytical skills in natural sciences and environmental pollution material.